Epidemiological trends of malaria infection in Jeddah, Saudi Arabia, 2018-2023 - Alghamdi, Rana; Bedaiwi, Ahmed; Al-Nazawi, Ashwaq M. (Frontiers in Public Health, 2024)
BackgroundMalaria poses a significant global public health challenge, especially in tropical regions. Saudi Arabia established the malaria elimination program decades ago, and implemented public health strategies to reduce malaria burden. Every year, Saudi Arabia welcomes millions of people worldwide, particularly from endemic countries, for work, religious activities, visits, and tourism. Jeddah city plays a vital role as a logistical center for the entry of travelers through its airports and seaports. Gaining insight into the demographic characteristics of malaria cases in Jeddah governorate is a crucial assessment for public health measures to reduce the malaria burden and support the malaria elimination program.MethodIn this cross-sectional study, we described the characteristics of malaria cases reported by the Vector-Borne and Zoonotic Diseases Administration in Jeddah from 2018 to 2023. We also conducted a descriptive analysis using R and QGIS software to comprehend the epidemiological status of malaria cases in the Jeddah governorate.ResultsA total of 2,124 cases were reported from 2018 to 2023. Pakistanis are considered the major nationality with malaria by 47.56%. African countries such as Sudan, Ethiopia, Nigeria, and Chad showed more than a third of malaria cases reported. Plasmodium Vivax and Falciparum were reported by almost 57 and 38%, respectively. An increasing number of malaria cases observed every year, except during the COVID-19 pandemic.ConclusionThis study illustrated the epidemiology trend of malaria cases reported in Jeddah city between 2018 and 2023. Its findings highlighted the importance of strengthened emphasis on malaria prevention protocols in the Kingdom of Saudi Arabia.